Broken or Just Bent? Rethinking Tribhuvan University’s Examination System - Neupane, Ram Nath (Tribhuvan Journal, 2025)
Teaching and examination are inseparable parts of learning. Examination should evaluate overall learning achievements of students. However, the examination system at Tribhuvan university has been often criticized for not clearly assessing learning achievements of students. Therefore, the present study aims to investigate the perspectives of teachers, students, parents, and administrators regarding the current examination system at Tribhuvan University. Data were purposively collected from the stakeholders to get the intended information using questionnaire. The findings reveal that teachers at Tribhuvan University recognized the standardized nature of exams,however, they received limited training in innovative assessment practices.Teachers employ alternative assessment approaches, such as oral presentations, writing projects, and peer assessment in the internal assessment of semester-based programs. Many students recognize that examinations are stressful, because they focus on memorization, and rote learning which can limit the opportunities for critical thinking, skill application, or holistic learning. Challenges, such as academic dishonesty, irregularities, and unfairness in the exams, limit the implementation. Parents emphasize student-centred and continuous assessment practices. Administrators focus on the academic and administrative honesty while conducting examinations despite facing the problems such as limited infrastructure, and digitization that can hinder well assessment delivery.The study suggests to employ alternative and continuous evaluation approaches, improve teacher capacity in assessment and promote fairness and transparency in the examination system.